Importance of clinical trials and contributions to contemporary medicine: commentary - Haofuzi Zhang; Xiaofan Jiang (Annals of Medicine)
Clinical trials are crucial to contemporary medicine, offering valuable insights into the safety, efficacy, and appropriate use of new treatments. They contribute to public health improvements, reduce healthcare costs, uncover new understandings of disease biology, and facilitate the development of therapies for rare conditions. Investing in clinical trials is therefore essential for advancing medical science and enhancing patient outcomes globally.